ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUSAHA UMK UNTUK MENGGUNAKAN JASA PEMBIAYAAN MODAL KERJA PADA BANK SYARIAH DI KOTA MEDAN - Renol Lubis; Kasyful Mahalli (Ekonomi dan Keuangan, 2014)
The problems of this study are the factors that influence the micro and small entrepreneurs (MSEs) to use the services of working capital financing in Islamic banks in the city of Medan and how these factors influence the SME entrepreneurs to use the services of capital financing work on Islamic Banking.As for the object of this research is the MSE entrepreneurs in the city of Medan. The data used in this study is primary data obtained from questionnaires directly. The sample used in this study were 95 samples with a stratified sampling method.Results of primary data processing with methods of descriptive statistics showed that most respondents agreed that if the factor procedure and factors affecting service is influencing them to use the services of working capital financing in Islamic banks and to be neutral to the belief factor.Keywords: Procedure, Faith, Services, Islamic Banking, SME Entrepreneurs